Analysis of cassava value chain in Ghana: Implications for upgrading smallholder supply systems - Darko-Koomson, Samuel; Aidoo, Robert; Abdoulaye, Tahirou (Emerald Publishing Limited, 2020)
Commercialization of cassava is increasing because of increased urban demand for processed products and increased recognition of the industrial potential of the crop. This study aims to examine the cassava value chain in Ghana and its implications for upgrading.A combination of purposive, simple random and snowball sampling methods was adopted to select key actors in the cassava value chain. A semi-structured questionnaire was used to collect primary data. Analysis of the data was largely descriptive, except for profitability of cassava production in selected regions, which was examined by employing gross and net marketing margin analysis. A comprehensive value chain map was generated to show the different product pathways for cassava from the farm gate to the final consumer, and roles of key value chain actors and their relationships were summarized through simple narrations.Evidence has shown chains of more than four different channels through which fresh cassava roots move from the farm gate to final consumers. Production of cassava in Ghana is profitable, generating positive net marketing margins across major producing centres. Processing of cassava has both dry and wet/fresh value chains depending on the derived products for the final consumer. There is weak governance system in the cassava value chain in Ghana as majority of actors use spot market transactions in dealing with trading partners. The use of standardized grading and weighing system is very limited in the chain, and limited access to credit is a critical constraint to value chain upgrading.With the exception of results from the profitability analysis of producers, the findings on marketing margins of other value chain actors may not be generalizable. Future studies could determine the profitability associated with cassava value-adding activities like processing into various forms and explore the possibility of converting waste from processing into energy.The study includes implications that focus on product and process upgrading efforts by smallholders in the cassava value chain. This paper recommends innovative financing models for smallholders to improve access to microcredit via internal and external funding sources.This paper reveals specific intervention areas in which smallholders can direct efforts in an attempt to improve the cassava value chain through product, process and functional upgrading.